Approach to the synthesis of new analogue of sildenafil towards palladium-catalyzed 3-methylsulfanyl-1,2,4-triazine - boronic acid cross coupling (The All Results Journal, 2014)
In the search for more potent and selective PDE5 inhibitors, approach to the synthesis of new sildenafil analogue 2 characterized by the presence of the pyrazolo[4,3-e][1,2,4]triazine core and ethylamino group in the 2’ position on the phenyl ring was designed.